2009
DOI: 10.1186/1476-9255-6-18
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α and IL-10 downregulation and marked oxidative stress in Neuromyelitis Optica

Abstract: Background: Neuromyelitis optica is a central nervous system demyelinating and inflammatory syndrome. The objective of this study is to identify cytokines related to the cellular immune response as well as blood brain barrier integrity and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 36 publications
(32 reference statements)
2
36
0
Order By: Relevance
“…Simultaneously, the CSF sCD27 concentrations had a significantly positive correlation with CSF TP in NMOSD. This is consistent with the positive correlation between CSF sCD27 and proinflammatory cytokines (e.g., IL-6) [32], as well as the negative correlation between CSF sCD27 and anti-inflammatory cytokines (e.g., IL-10) [33]. Therefore, CSF sCD27 is a marker for inflammatory activity in NMOSD.…”
Section: Discussionsupporting
confidence: 68%
“…Simultaneously, the CSF sCD27 concentrations had a significantly positive correlation with CSF TP in NMOSD. This is consistent with the positive correlation between CSF sCD27 and proinflammatory cytokines (e.g., IL-6) [32], as well as the negative correlation between CSF sCD27 and anti-inflammatory cytokines (e.g., IL-10) [33]. Therefore, CSF sCD27 is a marker for inflammatory activity in NMOSD.…”
Section: Discussionsupporting
confidence: 68%
“…It is speculative that free radical oxygen chemistry may contribute to the pathogenesis in this condition [18]. Pentón-Rol et al [19] found almost undetectable levels of TNF-a, a decreased production of IL-10 and a significant up-regulation of every OS biomarker in NMO. Her results suggested that a TNF-a and IL-10 down-regulation and marked OS existed in NMO.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies suggested that reactive oxygen species may play a role in the pathogenesis of NMO. The evidence for the existence of oxygen species within inflammatory demyelinating lesions includes the presence of both lipid and protein peroxides, which involves the activation of PLA2 [40]. Therefore, the inhibition of PLA2 and the binding of NMO-IgG and AQP4 by isotetrandrine may both contribute to the inhibition of NMO.…”
Section: Discussionmentioning
confidence: 99%